Oil Price, Gold Price, Exchange Rate and Stock Market in Iraq Pre-During COVID19 Outbreak: An ARDL Approach - Asaad, Zeravan Abdulmuhsen (International Journal of Energy Economics and Policy, 2021)
This study used the econometrics methods to identify the interactions among oil price, gold price, exchange rate, and stock price which represented by the (ISX60) index under the Iraq stock exchange pre-during global pandemic of COVID19. The analysis employed daily data which categorized into three time periods: full sample pre-during COVID19 from 24 December 2018 to 3 September 2020, the pre-COVID19 period from 31 December 2018 to 30 December 2019, as well as during-COVID19 from 27 December 2019 to 3 September 2020 in order to measure the interactions between the variables for each period. To accomplish that the study used the correlation matrix, unit root test to assure the stationary for the ARDL model and the granger causality test. The correlation output showed different results between the variables based on the period division. Furthermore, the study results accepted the null hypothesis of no cointegration exists between the variables respectively for the (Full sample Pre-during and pre-COVID19) period, and no decision could be made about the long-run relationship amongst the variables for the (during-COVID19) period, while the results of the causal short-run model showed that effect of oil price, gold price and exchange rate insignificant with Iraq stock exchange. Keywords: COVID19 Outbreak, Oil Price, Gold Price, Exchange Rate, Stock Market JEL Classifications: F31, C01, G12, G15 DOI: https://doi.org/10.32479/ijeep.11552